Focus Group Discussion Tentang Evaluasi Assessment Center dan Peluang Development Center dalam Pengembangan Talent Pegawai di PT PLN (Persero) - Ruditaningtyas Mijil Retno Ayu Mumpuni (Universitas Muhammadiyah Jember, 2023)
Assessment center is still believed to be a reliable soft competency measurement method, not least at PLN. From the results, a person's soft competency is known. However, it is not enough for development of a talent. There needs to be a transformation of this method so that it becomes more comprehensive. This study wants to reveal development center opportunities in employee talent development based on the evaluation results of assessment center that has been carried out so far. FGD was chosen as the data collection method while data analysis was carried out through thematic analysis. The result found that development center can be an answer that can improve the assessment center where feedback is an integral part of assessment center process series. Providing feedback is followed up with employee self-development that can be achieved and monitored so that success can be measured.